ANALISIS DAMPAK PENINGKATAN BELANJA PEMERINTAH TERHADAP PENYERAPAN TENAGA KERJA DI INDONESIA - Shofwatun Hasna (Journal Of Communication Education, 2016)
ABSTRACTThis study aims to analyze the influence of government spending toward employment growth in Indonesia for six years (2010-2015). This study is using the panel data from 18 provinces in Indonesia. The panel model chosen is fixed effect. The research finding indicated that the employment growth in Indonesia had been growing down since research periode. The government spending has positive impact to productivity growth, but it has negative impat to employment growth. It’s done because the government spending impact to increasing domestic exchange rate, and decreasing export value, so impact to decreasing employment growth. Many firms have also grown their productivity by increasing the capital and decreasing the labor, and many labors at many firms are become from foreign and decrease the domestic labor.Keyword: government spending, productivity growth, employment growth.